2018
DOI: 10.18203/2394-6040.ijcmph20182416
|View full text |Cite
|
Sign up to set email alerts
|

Study on consumption of fast food among medical students of IGIMS, Patna

Abstract: Background: Fast food culture is a vigorously uprising trend among the youngsters and medical students are no exception to it. Stressful life due to increased study load negatively influences the food choices of medical students. Hence the present study was undertaken with objectives to figure out the prevalence of fast food consumption among medical students, to study the fast food consumption pattern by the medical students and to explore various factors contributing to fast food consumption by the students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
1
5
1
Order By: Relevance
“…This finding is in accordance with a previous Malaysian study which revealed that 73.5% of medical students consumed fast food more than two times per week (Rydell et al, 2008). Also, it is consistent with another study which discovered that all students continue to consume fast food while they are aware that consuming fast food might result in several illnesses and disabilities (Shree et al, 2018). Eating white bread among the medical students decreased significantly from 74.8% to 66.9% (P =.045).…”
Section: Medical Science L Analysis Articlesupporting
confidence: 91%
“…This finding is in accordance with a previous Malaysian study which revealed that 73.5% of medical students consumed fast food more than two times per week (Rydell et al, 2008). Also, it is consistent with another study which discovered that all students continue to consume fast food while they are aware that consuming fast food might result in several illnesses and disabilities (Shree et al, 2018). Eating white bread among the medical students decreased significantly from 74.8% to 66.9% (P =.045).…”
Section: Medical Science L Analysis Articlesupporting
confidence: 91%
“…11.66% students in our study were regularly eating outside (i.e.>5 meals outside home/week) which is quite less as reported by others [9,10] . Reasons like easy access to eating facilities and outside eateries offering a lot of meal choices can drive students towards eating outside.…”
Section: Discussioncontrasting
confidence: 51%
“…Similar observations were seen in a study done in Patna (100%), Jammu and Kashmir (100%), Lucknow (98%) and China (97.5%). [8][9][10][11] Driskell et al found that soft drinks were the most frequently consumed by female college students. 12 Similar was the finding in the present study, however the incidence was the same among both boys and girls.…”
Section: Discussionmentioning
confidence: 99%